RNA:RNA interaction can enhance RNA localization in Drosophila oocytes. - Hartswood, E; Brodie, J; Vendra, G; Davis, I; Finnegan, D (2012)
RNA localization is a key mechanism for targeting proteins to particular subcellular domains. Sequences necessary and sufficient for localization have been identified, but little is known about factors that affect its kinetics. Transcripts of gurken and the I factor, a non-LTR retrotransposon, colocalize at the nucleus in the dorso-antero corner of the Drosophila oocyte directed by localization signals, the GLS and ILS. I factor RNA localizes faster than gurken after injection into oocytes, due to a difference in the intrinsic localization ability of the GLS and ILS. The kinetics of localization of RNA containing the ILS are enhanced by the presence of a stem-loop, the A loop. This acts as an RNA:RNA interaction element in vivo and in vitro, and stimulates localization of RNA containing other localization signals. RNA:RNA interaction may be a general mechanism for modulating RNA localization and could allow an mRNA that lacks a localization signal to hitchhike on another RNA that has one.